Parsing impulsivity in individuals with anxiety and depression who use Cannabis. (1st December 2020) - Spechler, Philip A.; Stewart, Jennifer L.; Kuplicki, Rayus; Paulus, Martin P.; ,
Highlights: Impulsivity profiles of cannabis using anxious/depressed patients is understudied. Patients were compared to matched very-low cannabis users and healthy controls. Multiple facets of impulsivity were interrogated. A propensity to act rashly when experiencing strong affect was found in patients. Bayes factor analysis indicated substantial support for the null fMRI results. Abstract: Background: Individuals with anxiety/depression may impulsively use cannabis to acutely induce positive affect and attenuate aversive mood states. However, few studies have attempted to parse impulsivity displayed by anxious/depressed cannabis users. This investigation examined what aspects of impulsivity characterize those individuals using self-report and functional MRI (fMRI) measures. Methods: Individuals with any lifetime anxiety/depression diagnoses and problematic cannabis use ("Anx/Dep+CB"; n =42) were compared to a propensity score-matched group with very low cannabis use ("Anx/Dep-lowCB"; n =42), and a healthy control group ( n =37). Impulsivity was measured using the UPPS-P Impulsivity Questionnaire and the Stop Signal Task (SST) during fMRI. For UPPS-P, regression models estimated group-by-impulsivity subscale interactions with post-hoc pairwise tests. For the SST, similar regression models were estimated with four a-priori regions of interest (ROIs; right opercularis, orbitalis, dorsal and ventral anterior insula) during stop-success and stop-failure processing. Null SST findings were followed up using Bayes factor analysis to quantify the evidence in support of the null hypothesis. Results: For the UPPS-P, a significant group-by-subscale interaction indicated that the Anx/Dep+CB group exhibited higher levels of impulsivity on the negative- and positive-urgency subscales relative to both comparison groups. Higher negative-urgency correlated with heavier lifetime cannabis use across groups. For the SST, there were no ROI task activation differences. Bayes factor analysis determined the null findings were at least three times more likely than the alternative hypothesis for all ROIs. Conclusions: Impulsivity under periods of heightened affect, but not motor response inhibitions, characterized anxious/depressed individuals who use cannabis.